Energy Consumption, Economic Growth and CO2 Emissions in Middle East - Alkasasbeh, Omar M.; Alassuli, Abdalla; Alzghoul, Amro (International Journal of Energy Economics and Policy, 2023)
Energy consumption nowadays has become a global concern for excess Carbon dioxide emission. Excess CO2 emission has created a major concern regarding global environmental sustainability. Middle Eastern countries are well-known for their energy production through fossil fuel consumption. The present research has focused on analysing the impact of CO2 emission, energy consumption and economic growth in Middle Eastern countries. Five countries have been selected for this research United Arab Emirates, Iran, Kuwait, Qatar, and Turkey. Heterogeneity and cross-sectional dependency in the study variables were addressed using second-generation econometric approaches. The cointegration approach developed by Westerlund and Edgerton (2008) proved the existence of a long-run equilibrium among variables in the presence of structural breaks. Environmental carbon emissions rise as a result of economic growth The results prove that alternative sources of energy consumption should be employed to achieve environmental and economic sustainability.